Quasi-Conformally Flat α - Sasakian Manifold Under Schouten-Van Kampen Connection - Sil, Amit (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study focuses on pseudo-quasi conformally α-Sasakian manifolds via Schouten-van Kampen connection (in short SK connection). We also investigate ϕ pseudo quasi-conformally flat α-Sasakian manifolds via the SK connection. Subsequently, we investigate a distinctive curvature condition for α-Sasakian manifolds with the SK connection.